2016
DOI: 10.15244/pjoes/60108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Quality for Yielding and Biometric Features of Miscanthus x Giganteus

Abstract: In recent years renewable energy sources (RES) have played a key role in current strategies to mitigate the impacts of global warming and independence on foreign energy sources. Miscanthus (Miscanthus x giganteus) is one of perennial grass which was identified as among best choices for low input bioenergy production. Our paper presents the relationship between the quality of soil and yielding as well as the biometrics features of miscanthus (Miscanthus x giganteus). Following this study Miscanthus x giganteus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…Bioenergy accounts for up to two-thirds of all RES in Europe, and it grows at a rate similar to that of all the other sources combined (AEBIOM, 2015). Another consequence of this is an increased scientific interest in lignocellulosis biomass, resulting in abundant literature on the subject (Mitsui et al, 2010;Weger et al, 2013;Sabatti et al, 2014;Manzone et al, 2015;Stolarski et al, 2015b;Matyka and Kuś, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bioenergy accounts for up to two-thirds of all RES in Europe, and it grows at a rate similar to that of all the other sources combined (AEBIOM, 2015). Another consequence of this is an increased scientific interest in lignocellulosis biomass, resulting in abundant literature on the subject (Mitsui et al, 2010;Weger et al, 2013;Sabatti et al, 2014;Manzone et al, 2015;Stolarski et al, 2015b;Matyka and Kuś, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Визначено, що генотипи міскантусу здатні знижувати викиди і виділяти на 40-99% менше закису азоту (N 2 O) відносно однорічних звичайних культур (Di Vita, Pilato, Pecorino, Brun, & D'Amico, 2017). Посіви Miscanthus × giganteus досягають повної потенційної врожайності, незалежно від ґрунту, починаючи з третього року вегетації (Alexopoulou et al, 2015;Matyka & Kus, 2016). Відомо також, що будь-яка поживна реакція ґрунту значно залежить від його фізико-хімічних властивостей, кліматичних умов (Souri, 2016;Souri, Sooraki, & Moghadamyar, 2017;Hatamian, Rezaie Nejad, Kafi, Souri, & Shahbazi, 2019) і місця посадки ризом міскантусу (Anderson et al, 2011).…”
Section: вступunclassified
“…According to results from Poland, it was found that to obtain high yields Miscanthus giganteus does not need cultivation on the best agricultural soils. This plant has the best yields on soils of average quality, not too heavy [30]. In Serbia, the highest yields were achieved on Gleysol [29] and carbonate chernozem [31].…”
Section: Characteristics Of Substratesmentioning
confidence: 99%